anonymous
  • anonymous
Y = X*X - 6X + 8 Let A = the value when X is Zero Let B = the largest value when Y = 0 Let C = the smaller value when Y = 0 THEN GO TO: N27 26.A(3*C)(A+1)W82 33.A(2*B)C+1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
what is this? N27 26.A(3*C)(A+1)W82 33.A(2*B)C+1
anonymous
  • anonymous
Coordinates for a Geocache.
anonymous
  • anonymous
I can figure out the coordinates equation but the first part I don't know how to do.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
I can help yo find A, B, and C. For A plug in 0 for x. For B and C, factor \(x^2-6x+8=0\) Find two numbers that multiply to 8 and add up to -6
anonymous
  • anonymous
I understand B and C, but I'm still confused about A. Could you explain that further please?
anonymous
  • anonymous
You substitute 0 for the x in the equation, then simplify to get y Y=0² -6(0)+8
anonymous
  • anonymous
Y=8?
anonymous
  • anonymous
yes. so A = 8 What did you get for B and C?
anonymous
  • anonymous
B=-2 C=-4
anonymous
  • anonymous
Start with this \(x^2-6x+8=0\) Use the two numbers you found to factor \((x-4)(x-2)=0\) Set each of the factors equal to 0 \(x-4=0\) or \(x-2=0\) Solve the equations for x \(x=4\), \(x=2\) So B = 4, C = 2
anonymous
  • anonymous
Oh that makes sense thank you very much!
anonymous
  • anonymous
you're welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.